2020
DOI: 10.1017/ice.2020.368
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal coinfections in COVID-19 patients hospitalized during the New York City pandemic surge

Abstract: We observed bacterial or fungal co-infections in COVID-19 patients admitted between March 1 – April 18, 2020 (152/4267, 3.6%). Mortality was 57%; 74% were intubated; 51% with bacteremia had central venous catheters. Time to culture positivity was 6-7 days; 79% received preceding antibiotics. Metallo-beta-lactamase-producing E. cloacae co-infections occurred in 5 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
223
4
19

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(271 citation statements)
references
References 8 publications
25
223
4
19
Order By: Relevance
“…The COVID-19 cluster showed antibiotic use that was 2-3-fold higher than overall consumption. Nori et al 4 found widespread antibiotic use in most hospitalized COVID-19 patients, similar to our study. Difficulty in differentiating COVID-19 from other infections may explain empirical treatment, but it does not justify maintenance on antibiotics after SARS-CoV-2 identification.…”
Section: Discussionsupporting
confidence: 92%
“…The COVID-19 cluster showed antibiotic use that was 2-3-fold higher than overall consumption. Nori et al 4 found widespread antibiotic use in most hospitalized COVID-19 patients, similar to our study. Difficulty in differentiating COVID-19 from other infections may explain empirical treatment, but it does not justify maintenance on antibiotics after SARS-CoV-2 identification.…”
Section: Discussionsupporting
confidence: 92%
“…The higher rate of antimicrobial use may be due to initiation of empiric therapy for suspected pneumonia or sepsis, consistent with guidelines for the latter [ 30 ]. Other studies have also observed higher utilization of antibiotics in patients with SARS-CoV-2 with no identified coinfection [ 4 , 31 , 32 ]. Although most drug classes were used at comparable levels in the different groups, the use of macrolides was much higher in SARS-CoV-2-positive patients.…”
Section: Discussionmentioning
confidence: 94%
“…1 Another single-center study from Spain showed increased use of amoxicillin-clavulanate during the early phase of the pandemic, followed by later increased utilization of broad-spectrum antibiotics. 2 There are several potential explanations for the observed increases in antimicrobial use including concerns of bacterial co-infection in suspected or newly diagnosed COVID-19 patients, increased risk of nosocomial infection due to administration of immunomodulatory therapy, reluctance to obtain diagnostic respiratory specimens, 3 diversion of clinical resources from stewardship activities during a time of crisis, and an increased proportion of hospitalizations being due to respiratory infections which typically prompt antibiotic therapy. Our finding that increases in antibiotic use were generalized across the VA and not restricted to facilities in areas with the highest case burden of COVID-19 suggests that issues not directly related to the care of COVID-19 patients contribute to the increased density of antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of increased antibiotic use during the COVID-19 pandemic have generally been from heavily impacted facilities or geographic regions and provide few details regarding patterns of antibiotic use. [1][2][3] To provide a broader overview of changes in antibiotic use in a healthcare system with a long-standing enterprise-wide commitment to antibiotic stewardship, we compared patterns of antibiotic use throughout the VA from January-May 2020 with corresponding time periods in prior years.…”
Section: Introductionmentioning
confidence: 99%